(untitled) (Bangladesh Journal of Otorhinolaryngology, 2011)
Introduction: To evaluate the demographic pattern types, motives and its consequences of cut throat injury. Methods: This prospective observational study was conducted in the department of ENTHead & Neck Surgery at Dhaka medical college hospital, Dhaka, from January 2009 to June 2010, among 67 admitted cases of cut throat injury victims. Results: Among 67 cases, 47 were male and 20 were female, aged between 7 – 73 years (mean 28.82±11.38). Majority of victims were young adult 41 (61.19%), aged between 21 to 30 years, 52(77.61%) were from rural community and 53(79.10%) were belong to the low socioeconomic class. Homicide was commonest (71.64%) cause. Only 7 (10.44%) victims had suicidal attempt for doing self cut, where female out numbered. Political conflict (22.38%) and the land dispute (25.37%) were the major contributory factors behind the homicidal cut throat injuries. 50 (74.63%) victims were injured at the zone-II level of the neck. 34(50.75%) victims were injured in larynx. Emergency tracheostomy needed among 38 (56.72%) victims and blood transfusion needed among 30(44.78%) cases for haemorrhage. Majority stayed less than two week duration (80.59%) in the hospital. As the consequence of this injury 8.96% victims died due to haemorrhagic shock, aspiration pneumonitis & septicaemia. Conclusion: Social and political motivation, increase literacy rate and economical growth along with improvement of law and order of the land prevent vast majority from homicidal cut throat. Early interference in an improved management set up with surgical intervention may reduce the mortality and morbid consequences. Key words: Cut throat injury; Neck injury; Penetrating neck injury. DOI: 10.3329/bjo.v17i1.7616 Bangladesh J Otorhinolaryngol 2011; 17(1): 5-13